The Skin May Clear But the Arthritis Won’t Disappear: Focusing on Concomitant and New-Onset Psoriatic Arthritis in a Daily Practice Cohort of Psoriasis Patients on Biologic Therapy - van Muijen ME; van Hal TW; Groenewoud HMM; van den Reek JMPA; de Jong EMGJ (Dove Medical Press, 2020)
Marloes E van Muijen, 1, 2 Tamara W van Hal, 1– 3 Hans MM Groenewoud, 2 Juul MPA van den Reek, 1, 2 Elke MGJ de Jong 1, 2, 4 1Department of Dermatology, Radboud University Medical Center (Radboudumc), Nijmegen, the Netherlands; 2Radboud Institute for Health Sciences (RIHS), Radboud University Medical Center (Radboudumc), Nijmegen, the Netherlands; 3Department of Rheumatology, Sint Maartenskliniek, Nijmegen, the Netherlands; 4Radboud University, Nijmegen, the NetherlandsCorrespondence: Marloes E van Muijen Email Marloes.vanMuijen@radboudumc.nlBackground: Previously identified risk factors for psoriatic arthritis (PsA); nail dystrophy and scalp lesions are highly prevalent in patients with moderate-to-severe psoriasis. Therefore, these variables may not be useful as predictors for PsA in this population.Objective: We assessed the predictive value of demographic and clinical characteristics for development of PsA in a cohort of patients with moderate-to-severe psoriasis, currently treated with biologics. Furthermore, we reported the incidence of new-onset PsA in this population and described the characteristics of patients that developed PsA during biologic treatment.Methods: Demographics and treatment characteristics of psoriasis patients currently using biologic therapy were extracted from the BioCAPTURE database (n=427). Poisson regression was used to calculate incidence rates. Multivariable logistic regression was performed to identify factors independently associated with PsA onset. Patient and treatment characteristics of patients that developed PsA during biologic treatment were described.Results: The incidence of PsA was 1.0 (95% CI 0.8– 1.2) per 100 psoriasis-years. Except for a lower risk for PsA in male gender (OR 0.58, 95% CI 0.34– 0.98, p-value 0.04), no clinical factors were significantly associated with an altered risk of developing PsA. During biologic therapy, 32 patients (9.4%) newly developed PsA. In this group, 53.8% had PASI< 5 at PsA diagnosis. The incidence rate of PsA was 1.6 (95% CI 1.1– 2.2) per 100 years on biologic therapy.Conclusion: Clinical risk factors might be inaccurate to predict PsA onset in patients with moderate-to-severe psoriasis on biologics. Even with low disease activity, psoriasis patients on biologics are still prone to develop PsA.Keywords: psoriasis, psoriatic arthritis, risk factors, biologic therapy, phenotype, localization